Inventory development to assess perceptions and metacognition of dental students toward learning in colleges in Pune, India - Shruti P Nair; Sahana Hegde Shetiya; Deepti Agarwal; Ladusingh Rajpurohit (Journal of Education and Health Promotion, 2022)
BACKGROUND: Dental education is considered a challenging and taxing program as on successful completion one is required to attain unique and diverse competencies. There is an established perception that students do not enjoy their experiences in the dental institution and they always demand for certain amendments. Therefore, a dental education perceptions and metacognition assessment tool (DEPMAT) was developed for Indian undergraduate and postgraduate dental students for assessing their learning in Deemed University versus Maharashtra University of Health Sciences in Pune, Maharashtra. MATERIALS AND METHODS: This cross-sectional study was conducted among students of four dental colleges of two types of universities in Pune, India, using a 31-item DEPMAT based on Dundee Ready Education Environment Measure and metacognition awareness inventory using five subscales. Psychometric properties were also tested for this new tool. Data were analyzed using the SPSS software. RESULTS: Of 512 participants, 498 (96.88%) students had duly returned the questionnaire. Cronbach's alpha coefficient value for reliability was found to be 0.87 which indicated good internal consistency and test-retest reliability was found to be kw = 0.76, which indicated substantial agreement. Significant difference was found among undergraduates in domains regarding their perception toward academics, infrastructure and learning environment, and health and stress. CONCLUSION: This study suggested that the general perception toward learning among final year postgraduate students was positive in both the universities. However, the perception of final year undergraduates toward learning was negative and students have suggested certain amendments in both the universities. This study also suggested the new tool was effective in assessing the attitude of practice of both undergraduate and postgraduate students.